2021
DOI: 10.3389/fneur.2021.659922
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Derived Growth Factor-AA Correlates With Muscle Function Tests and Quantitative Muscle Magnetic Resonance in Dystrophinopathies

Abstract: Introduction: Duchenne (DMD) and Becker (BMD) muscular dystrophy are X-linked muscular disorders produced by mutations in the DMD gene which encodes the protein dystrophin. Both diseases are characterized by progressive involvement of skeletal, cardiac, and respiratory muscles. As new treatment strategies become available, reliable biomarkers and outcome measures that can monitor disease progression are needed for clinical trials.Methods: We collected clinical and functional data and blood samples from 19 DMD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…To explore potential relationships between our differential gene expression and reported mechanisms of DMD pathology that can be mapped to individual genes, we analyzed the differential expression of previously reported human serum/blood DMD biomarkers (Hathout et al, 2014;Parolo et al, 2018;Spitali et al, 2018;Al-Khalili Szigyarto, 2020;Grounds et al, 2020;Alonso-Jiménez et al, 2021;Wagner et al, 2021;Lee-Gannon et al, 2022;Wu et al, 2022), and of genes modifying the phenotype of DMD in humans (Pegoraro et al, 2011;Flanigan et al, 2013;Bello et al, 2016;Hogarth et al, 2017;Li et al, 2018;Weiss et al, 2018;Spitali et al, 2020;Flanigan et al, 2023) or the mdx mouse (Deconinck et al, 1997;Wagner et al, 2002;Han et al, 2011;Morales et al, 2013;de Zélicourt et al, 2022), also known as genetic modifiers, across the VL and TA and identified the predominant cell type in which they were expressed.…”
Section: Genes That Are Previously Reported As Dmd Biomarkers and Gen...mentioning
confidence: 99%
“…To explore potential relationships between our differential gene expression and reported mechanisms of DMD pathology that can be mapped to individual genes, we analyzed the differential expression of previously reported human serum/blood DMD biomarkers (Hathout et al, 2014;Parolo et al, 2018;Spitali et al, 2018;Al-Khalili Szigyarto, 2020;Grounds et al, 2020;Alonso-Jiménez et al, 2021;Wagner et al, 2021;Lee-Gannon et al, 2022;Wu et al, 2022), and of genes modifying the phenotype of DMD in humans (Pegoraro et al, 2011;Flanigan et al, 2013;Bello et al, 2016;Hogarth et al, 2017;Li et al, 2018;Weiss et al, 2018;Spitali et al, 2020;Flanigan et al, 2023) or the mdx mouse (Deconinck et al, 1997;Wagner et al, 2002;Han et al, 2011;Morales et al, 2013;de Zélicourt et al, 2022), also known as genetic modifiers, across the VL and TA and identified the predominant cell type in which they were expressed.…”
Section: Genes That Are Previously Reported As Dmd Biomarkers and Gen...mentioning
confidence: 99%
“…Relative expression values were calculated by using the 2-CT method. Referring to the reference genes used in the previous study (De Pasquale et al, 2012;Hildyard et al, 2018;Alonso-Jimenez et al, 2021), we chose GAPDH, SDHA, HPRT1 and RPL13a as possible reference genes and determined the amount of their expressions in DMD and control groups by RT-qPCR. The web-based tool RefFinder 4 (Lu et al, 2018) was used to comprehensively evaluated the stability of candidate reference genes and GAPDH was shown as the most stable gene (Supplementary Figure 1), which was then chosen as an internal control.…”
Section: Real-time Quantitative Reverse Transcription Pcrmentioning
confidence: 99%
“…Treatment of murine models of DMD with tyrosine kinase inhibitors blocking the PDGFRα, such as imatinib, crenolanib, and nintedanib, decreased muscle fibrosis and improved muscle function 20–22 . Moreover, previous studies have shown that PDGF‐AA expression is higher in dystrophic compared with healthy muscles 23 and that PDGF‐AA serum levels are increased in DMD patients correlating with several muscle function tests 24 . However, the pathways activated by PDGF‐AA in FAPs in muscular dystrophies have not been described so far.…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 22 Moreover, previous studies have shown that PDGF‐AA expression is higher in dystrophic compared with healthy muscles 23 and that PDGF‐AA serum levels are increased in DMD patients correlating with several muscle function tests. 24 However, the pathways activated by PDGF‐AA in FAPs in muscular dystrophies have not been described so far. This knowledge could help us to identify new targets for therapies aiming to reduce fibrosis in DMD and slow down the on‐going degenerative process.…”
Section: Introductionmentioning
confidence: 99%